Punicic acid alleviates methylglyoxal-induced oocyte dysfunction during in vitro maturation in mouse species - Shahrzad Ronasi; Amir Hossein Mahdavi; Shiva Rouhollahi Varnosfaderani; Rasoul Kowsar; Farnoosh Jafarpour; Mohammad Hossein Nasr-Esfahani (PLoS ONE, 2025)
Dicarbonyl stress, characterized by the abnormal accumulation of reactive dicarbonyl metabolites and advanced glycation end-products (AGEs), is implicated in various pathological conditions, including obesity, diabetes, and reproductive disorders. Methylglyoxal (MGO), a highly reactive dicarbonyl metabolite, has been shown to compromise oocyte quality and developmental competence. In this study, we investigated the protective role of punicic acid (PA), a potent antioxidant found in pomegranate seed oil, against MGO-induced oocyte dysfunction. Our findings revealed that 75 µM MGO exposure during in vitro oocyte maturation significantly reduced the maturation rate and impaired subsequent embryonic development, characterized by decreased pronucleus formation and blastocyst rates. Interestingly, PA supplementation partially ameliorated these adverse effects of MGO, highlighting its potential as a protective agent against dicarbonyl-induced oocyte dysfunction. Co-treatment with PA restored the imbalanced redox state induced by MGO, leading to reduction in ROS levels and an increase in GSH levels in matured oocytes. Additionally, co-supplementation with PA preserved mitochondrial distribution in oocytes challenged with MGO, further contributing to improved oocyte quality. At the molecular level, PA co-treatment modulated the expression of genes involved in dicarbonyl stress and oxidative responses, including Glo1, Rage, Nrf2, and Nf-κB, potentially regulating the detoxification of MGO and mitigating its harmful effects. Lastly, PA supplementation improved cell lineage allocation in blastocysts developed from MGO-challenged oocytes, emphasizing its role in enhancing the quality of preimplantation embryos. In conclusion, our study provides novel insights into the protective effects of punicic acid as an antioxidant against MGO-induced oocyte dysfunction, suggesting its potential as a dietary intervention to enhance reproductive health, particularly in individuals facing dicarbonyl stress-associated conditions such as obesity and diabetes.